Successful maintenance therapy with tocilizumab for severe acute liver failure associated with adult-onset still’s disease - Koji Suzuki; Mitsuhiro Akiyama; Yukie Nakadai; Shingo Usui; Yuko Kaneko (Immunological Medicine, 2024)
Elevated liver enzymes are commonly observed among adult-onset Still’s disease (AOSD), but severe acute liver failure is extremely rare. Although severe acute liver failure associated with AOSD poses a life-threatening condition, the appropriate treatment is unclear. Some case reports have demonstrated the efficacy of high-dose prednisolone (PSL) and cyclosporin A (CyA), although the adverse effects of CyA led certain patients to cease its use. Therefore, an alternative treatment option is crucial, and thus far, there have been no reports of tocilizumab (TCZ) being used for this severe phenotype. Here, we report the first case of successful treatment using TCZ as maintenance therapy for severe ALF associated with AOSD. Following initial treatment with high-dose PSL and CyA, our case was switched to TCZ due to CyA-related side effects including alopecia and tremors. Our case highlights TCZ as a potential option for maintenance therapy of this severe condition.